Analysis of the DNA-Binding Activities of the Arabidopsis R2R3-MYB Transcription Factor Family by One-Hybrid Experiments in Yeast - Kelemen, Zsolt; Sebastian, Alvaro; Xu, Wenjia; Grain, Damaris; Salsac, Fabien; Avon, Alexandra; Berger, Nathalie; Tran, Joseph; Dubreucq, Bertrand; Lurin, Claire; Lepiniec, Loïc; Contreras-Moreira, Bruno; et al. (PloS one, 2015)
The control of growth and development of all living organisms is a complex and dynamic process that requires the harmonious expression of numerous genes. Gene expression is mainly controlled by the activity of sequence-specific DNA binding proteins called transcription factors (TFs). Amongst the various classes of eukaryotic TFs, the MYB superfamily is one of the largest and most diverse, and it has considerably expanded in the plant kingdom. R2R3-MYBs have been extensively studied over the last 15 years. However, DNA-binding specificity has been characterized for only a small subset of these proteins. Therefore, one of the remaining challenges is the exhaustive characterization of the DNA-binding specificity of all R2R3-MYB proteins. In this study, we have developed a library of Arabidopsis thaliana R2R3-MYB open reading frames, whose DNA-binding activities were assayed in vivo (yeast one-hybrid experiments) with a pool of selected cis-regulatory elements. Altogether 1904 interactions were assayed leading to the discovery of specific patterns of interactions between the various R2R3-MYB subgroups and their DNA target sequences and to the identification of key features that govern these interactions. The present work provides a comprehensive in vivo analysis of R2R3-MYB binding activities that should help in predicting new DNA motifs and identifying new putative target genes for each member of this very large family of TFs. In a broader perspective, the generated data will help to better understand how TF interact with their target DNA sequences.